2010
DOI: 10.1111/j.1467-839x.2010.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital satisfaction of Chinese under stress: Moderating effects of personal control and social support

Abstract: Stressful life events, personal control, and social support were examined relative to marital satisfaction among 1749 participants in seven Chinese cities. Stressful life events were categorized as life crises and life transitions. Life crises, rather than transitions, negatively predicted the marital satisfaction of Chinese. The moderating effects of personal control were found among women, but not men, and occurred only in the relationship between marital satisfaction and life crises, not life transitions. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 44 publications
2
28
1
6
Order By: Relevance
“…The significant positive relationship between perceived social support and resilience is consistent with the results of a number of previous studies (Armstrong, Bernie-Leftkovich and Ungar, 2005;Dent and Cameron, 2003;Xu and Ou, 2014). In an interesting study that examined marital satisfaction of Chinese under stress, an incidental finding showed that social support was a key factor in reducing the negative effects of life crises (Chi et al, 2011). Lee, Suchday and Wylie-Rosett (2012) stated that with the perception of a strong social support network, an individual was better able to cope with adverse situations, relative to someone who had to cope alone.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The significant positive relationship between perceived social support and resilience is consistent with the results of a number of previous studies (Armstrong, Bernie-Leftkovich and Ungar, 2005;Dent and Cameron, 2003;Xu and Ou, 2014). In an interesting study that examined marital satisfaction of Chinese under stress, an incidental finding showed that social support was a key factor in reducing the negative effects of life crises (Chi et al, 2011). Lee, Suchday and Wylie-Rosett (2012) stated that with the perception of a strong social support network, an individual was better able to cope with adverse situations, relative to someone who had to cope alone.…”
Section: Discussionsupporting
confidence: 77%
“…Perceived social support makes a person more resilient in times of stress and prevents a psychopathology from developing (Ozbay et al, 2007). It also equips an individual with the necessary resources to cope with a crisis (Chi et al, 2011). …”
Section: Social Support and Resiliencementioning
confidence: 99%
“…However, results revealed a main effect of initial perceived social support in predicting marital stress one year later. Taking into account the fact that outside support from family and community contexts can be a protective factor of the marital system (Patterson, 2002;Peilian et al, 2011), it seems that having high levels of perceived social support from relatives, friends or workmates can also decrease the stress associated to experiencing infertility exerted within the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of occupational stress and negative emotions lead to the formation of marital conflicts and increase the risk of separation in the future. Generally, researches show a negative relationship between occupational stress and marital satisfaction (Nasiri Zarin Ghabaei et al 2016, Rajabi et al 2013Chi et al, 2011). One solution to reduce occupational stress for nurses is supporting them.…”
mentioning
confidence: 99%
“…Researches indicate the influence of social support on stress reduction (Abualrub, Omarif, and Abualrub, 2009;Abualrub, 2004;Mohammadi Fakhar, Rafiei & Heshmat Haghani, 2012) and neutralizing negative effects of occupational stress on marital satisfaction (Conner, 2015;Chi et al, 2011;Abualrub et al, 2009). According to a decrease in the average duration of marriage, and obligation to have an imposed life, the ascending trend of divorce rate in recent years, and the dire consequences of marital conflict and divorce for family and community members, researchers and therapists are attempting to find the causes of social problems and methods through which it can be reduced and prevented.…”
mentioning
confidence: 99%